Quantitative Assessment of Receptors of Advanced Glycation End Products Expression in Tissue Samples from Patients with oral Submucous Fibrosis, Leukoplakia, and Oral Squamous Cell Carcinoma - Palati Sinduja; Pratibha Ramani; Saravanan Sekaran (Wolters Kluwer Medknow Publications, 2024)
Background and Aim: Oxidative stress markers have been firmly established as elevated in oral squamous cell carcinomas (OSCCs). These markers play a crucial role in the pathogenic mechanism underlying the accumulation of advanced glycation end products (AGEs) and their respective receptors. The primary objective of this study is to discern and compare the levels of receptors of AGEs (RAGEs) within tissue samples from patients diagnosed with oral submucous fibrosis (OSMF) at varying stages, oral leukoplakia at various stages, and OSCC. Materials and Methods: A cross-sectional investigation was conducted, enrolling a total of 49 patients, distributed across three distinct groups. Tissue samples were meticulously collected from the aforementioned patient groups. Subsequently, these samples underwent a process of homogenization and centrifugation. The supernatant obtained was subjected to enzyme-linked immunosorbent assay analysis to precisely determine the concentration of RAGE. Results: The concentration of RAGEs was found to be significantly higher at various stages of OSMF when compared to the reference group of OSCC (P < 0.05). This difference was statistically significant, indicating a substantial association. In contrast, the levels of RAGE in patients with hyperkeratosis accompanied by epithelial dysplasia at various stages were observed to be lower than those in the OSCC group, with the difference in concentration being statistically insignificant (P > 0.05). Conclusion: This comprehensive study has provided compelling evidence demonstrating the heightened levels of RAGE in OSMF when compared to OSCC. These findings collectively suggest the potential utility of anti-RAGE interventions as a promising avenue for novel therapeutic strategies in potentially malignant disorders such as OSMF.